Mrs. Ramsay's Knee - Anderson, Idris (Utah State University, University Libraries, 2008)
May Swenson Poetry Award Volume 12, with foreward by Harold Bloom. Mrs. Ramsay's Knee offers fresh and elegant poems by Idris Anderson, many of them ekphrastic considerations of visual works of art. Among her subjects are paintings by Rembrandt, Rousseau, Pollock, and Chagall, yet she equally explores a set of news photos from the 2006 war between Israel and Hezbollah.